A new species of cryptopone emery (hymenoptera: Formicidae: ponerinae) from Brazil with observations on the genus and a key for new word species - Fernandes, Itanna Oliveira; Delabie, Jacques H.C. (Sociobiology, 2019)
Cryptopone is a moderately large genus with 25 described species and subspecies. In the New World, only four species are known, C. gilva, C. guianensis, C. holmgreni and C. mirabilis. Recently four workers of an unidentified Cryptopone species were collected in the state of Rondônia, Brazil, in soil samples from the Floresta Nacional do Jamari (FLONA Jamari). These workers are described as Cryptopone pauli sp. nov. This is the first record of this genus for that state. We also present new records of Cryptopone for the Neotropical Region with some comments on its biology, systematics, and an updated key to the workers of Cryptopone in the New World. © 2019 Universidade Estadual de Feira de Santana. All rights reserved.